Current topics in developmental biology. Volume 42, Cumulative Subject Index to Vols. 20-41 - Pedersen, Roger A.; Schatten, Gerald; ScienceDirect eBooks (New York : Academic Press, 1999)
This Series provides a comprehensive survey of the major topics in the field of developmental biology. The volumes are valuable to researchers in animal and plant development, as well as to students and professionals who want an introduction to cellular and molecular mechanisms of development. The Series has recently passed its 30-year mark, making it the longest-running forum for contemporary issues in developmental biology.
Print version record.
Elsevier
Keywords: Embryology; Cytogenetics; SCIENCE -- Life Sciences -- Developmental Biology; Cytogenetics; Embryology; Electronic books